Sand training: Exercise-induced muscle damage and inflammatory responses to matched-intensity exercise. Issue 6 (3rd July 2017) - Brown, Henry; Dawson, Brian; Binnie, Martyn J.; Pinnington, Hugh; Sim, Marc; Clemons, Tristan D.; Peeling, Peter
Abstract: This study compared markers of muscle damage and inflammation elevated by a matched-intensity interval running session on soft sand and grass surfaces. In a counterbalanced, repeated-measures and crossover design, 10 well-trained female athletes completed 2 interval-based running sessions 1 week apart on either a grass or a sand surface. Exercise heart rate (HR) was fixed at 83–88% of HR maximum. Venous blood samples were collected pre-, post- and 24 h post-exercise, and analysed for myoglobin (Mb) and C-reactive protein (CRP). Perceptual ratings of exertion (RPE) and muscle soreness (DOMS) were recorded immediately post- and 24 h post-exercise. A significant time effect showed that Mb increased from pre- to post-exercise on grass ( p = .008) but not on sand ( p = .611). Furthermore, there was a greater relative increase in Mb on grass compared with that on sand ( p = .026). No differences in CRP were reported between surfaces ( p > .05). The HR, RPE and DOMS scores were not significantly different between conditions ( p > .05). These results suggest that in response to a matched-intensity exercise bout, markers of post-exercise muscle damage may be reduced by running on softer ground surfaces. Such training strategy may be used to minimize musculoskeletal strain while still incurring an equivalent cardiovascular training stimulus.